Gender-based violence in food systems - Treasure, Lilian; Forsythe, Lora; Martin, Adrienne (University of Greenwich, 2023)
Gender-based violence (GBV) is a significant global health and human rights issue, particularly for women and girls, with substantial social and economic costs. The sheer scale and endemic nature of GBV means that it touches virtually all aspects of life. However, its relationship to food systems—the complex networks of people and activities involved in food, from production to consumption—lacks recognition in research, policy, and civil society responses. In this paper, we present the initial findings from a systematic review and identify important gaps in evidence. This systematic review followed the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) statement updated in 2020. Our main research question for systematic review is: What empirical evidence is there on the incidence and prevalence of gender-based violence in agri-food systems? To answer this question our review explored how GBV was conceptualized in AFS; the prevalent forms; the drivers, risk factors, and impacts. Finally, we present the priorities for future research on gender-based violence research in agrifood systems.